NUMERICAL MODELING OF SEDIMENT TRANSPORTATION AT TANJUNG PRIOK PORT - Rahman, Fakhrur
Port of Tanjung Priok is one of the most important ports in Indonesia because it handles almost around 70% of the total flow of goods in Indonesia. Dredging the maintenance of the port pond which is routinely carried out annually with increasing volume is considered to be economically unfeasible in handling sedimentation problems that occur at the Port of Tanjung Priok. The scope of this research is to arrange numerical modeling configurations, calibration of water level elevations and flow velocity, hydrodynamic modeling, sensitivity analysis with river sediment concentration parameters, critical shear stress for deposition and critical shear stress for deposition, sediment transport modeling, calibration of sediment transport models, sediment transport modeling simulation, and determining alternative recommendations for sediment handling. The modeling process is carried out using MIKE21 software, for hydrodynamic simulations using the Hydrodynamic Module (HD), and sediment transport simulations using the Mud Transport Module (MT). Two modeling simulations were carried out, namely simulations for existing conditions and simulations with the addition of sediment retaining structures. Hydrodynamic simulation results show that the current pattern that occurs in the port ponds and shipping lines of the Tanjung Priok Port is relatively calm at high tide, but at low tide there is a movement of currents that carry sediment material into the port area. The results of the simulation of sediment transportation show a decrease in the volume of sediment material from 546,824.71 m3 / year to 452,434.64 m3 / year after the addition of the sediment retaining structure was carried out. These results indicate that dredging cost savings of Rp. 8,294,327,861.65 annually.